Using ISSR markers to build a phylogenetic of Barley Genotypes - M. Al_Hadeithi, Zeina S. (Iraqi Journal of Science, 2023)
This study is attempts to build a phylogenetic between nine Iraqi barleygenotypes based on ISSR-PCR analysis by determine the level of genetic similarityamong them. Nine issr primers used in this study produced 41 bands across ninestudied varieties. Of these bands, 28 bands were polymorphic and the remainingmonomorphic bands were 13. The average polymorphic rate was 70.5% rangedbetween 25%-100% , and average of polymorphic bands /primer was 4.5.The sizeof the amplified bands ranged 140-1600 bp. It was generated a 5 unique bands inthis study, these bands can be used as a DNA profiling of all studied genotypes. Theresults were showed Genetic distances ranged between (0.0854-0.9897) amongbarley varieties. Based on phylogenic tree, a dendrogram were constructed amongstudied barley varieties, cluster analysis grouped the nine varieties into two mainclusters depending on their ancestors and their morphological traits. The use ofcultivars from various clusters and sub clusters offer the possibility of obtaining anappropriate genetic variability in hybrid population.